Comparing the Effectiveness of Mentalization Based Treatment and Positive Psychology Intervention in Mistrust and Alienation among Homeless Women - Zahra Setoodeh; Moosa Javdan; Nooshin Taghinejad (Iranian Journal of Educational Research)
Objective: The present investigation delves into the effectiveness of two distinct therapeutic modalities, namely Mentalization-Based Treatment (MBT) and Positive Psychology Intervention (PPI), in tackling issues of mistrust and alienation among homeless females. Methods: The methodology employed in this study was of a semi-experimental nature, characterized by an experimental design utilizing a pre-test/post-test approach with a control group. Participant selection was carried out through a random sampling technique, resulting in the recruitment of 60 individuals who were subsequently allocated randomly into three groups, each comprising 20 participants. Data collection utilized the Early Maladaptive Schemas (EMS) instrument. To assess the research hypotheses, multivariate analysis of covariance and Bonferroni post-hoc tests were conducted. Results: Following a meticulous analysis of post-intervention outcomes, a notable discrepancy in scores between the MBT and PPI cohorts was observed. Specifically, the MBT cohort exhibited a significant enhancement in contrast to the control group, while no substantial variance was detected between the PPI cohort and the control group. Conclusions: As a result, it is deduced from this study that MBT surpasses PPI significantly in alleviating the mistrust and alienation schema prevalent in homeless women. In view of these findings, it is recommended that organizations supporting homeless women, particularly single mothers, contemplate the implementation of the Mentalization-Based Treatment strategy to augment their cognitive schemas and foster psychological well-being.